PROGRAMS OF SOCIO-ECONOMIC AND POLITICAL REFORMS OF KHOREZM JADIDS - Bekchanov Dоniyor (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes the socio-economic and political reform programs of Khorezm jadids. The main ideas of the Khorezm jadids, their role in the process of Social Development and their importance today are revealed.